Antioxidant activity of vernonia cinerea, peperomia pellucida and the combination of vernonia cinerea and peperomia pellucida / Sarini Ahmad Wakid and Nurul Syafiqah Zaharin - Ahmad Wakid, Sarini; Zaharin, Nurul Syafiqah (Universiti Teknologi MARA, Negeri Sembilan, 2020)
The present study was conducted to evaluate the antioxidant activity of Vernonia cinerea, Peperomia pellucida and combination of Vernonia cinerea and Peperomia pellucida. These two herbs are pants that often grow at random in different environments but are not commercialized due to the fact that no comprehensive study of the importance of their use. The extract was prepared with methanol respectively. 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay were used to study their antioxidant activity. The extracts were compared with commercial antioxidant, butylated hydroxytoluene (BHT). The highest scavenging effect from peel extract was presented by Vernonia cinerea with the value of 76.3% scavenging activity (IC50 = 2.909), followed by the combination of Vernonia cinerea and Peperomia pellucida (71.21% scavenging activity; IC50 = 5.274) and Peperomia pellucida with value of 68.3% scavenging activity (IC50 = 5.572). BHT showed the lowest IC50 value 1.71 with the scavenging activity 90.0%. Low IC50 value will indicates the strong ability of the extracts to act as DPPH scavenger.